2013
DOI: 10.1369/0022155413501324
|View full text |Cite
|
Sign up to set email alerts
|

Claudin 1 Expression Characterizes Human Uterine Cervical Reserve Cells

Abstract: Stem cells participate in cervical carcinogenesis but their function and exact features are still not clear. One type of stem-like cells are endocervical reserve cells (RCs), and their association with other normal/altered cervical cells is not exactly known. Epithelial cells are attached to each other by tight junctions. Their dominant components are the claudin proteins, which show changed expression in cancer; however, no data are available on their pattern. Expressions of various claudins (1, 2, 3, 4, 7), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…On the other hand, the expression of claudin-1 was reduced compared with that in the rest of the cervix in the invasive papillomas that developed in 7-month-old K14E7 mice treated with E 2 . These results are consistent with previous research which shows that claudin-1 is markedly expressed in grades I, II and III of human intraepithelial neoplasias, and in situ carcinomas ( 53 - 55 ), but decreases with progression to the invasive phenotype ( 56 ).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the expression of claudin-1 was reduced compared with that in the rest of the cervix in the invasive papillomas that developed in 7-month-old K14E7 mice treated with E 2 . These results are consistent with previous research which shows that claudin-1 is markedly expressed in grades I, II and III of human intraepithelial neoplasias, and in situ carcinomas ( 53 - 55 ), but decreases with progression to the invasive phenotype ( 56 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although a specific marker for reserve cells has yet to be identified [ 22 27 ], we considered p63, CK5 and CK8 as reserve cell markers because they serve as markers for basal stem cells, primary squamous cells and primary glandular cells, respectively. We first investigated a method to induce populations highly expressing p63 because p63 is known to be essential for the stemness of the epithelium in the basal layers [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…One limitation of our study was that we did not have any positive controls for the reserve cells. Because there is no definition for reserve cells, for example, in terms of gene expression patterns or gene expression levels, we could not demonstrate that the properties we induced were really reserve cells [ 10 , 22 24 , 27 ]. However, we showed a new approach for cervical CSC research, and in that sense, we can conclude that iRCs are potentially useful.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Biswas et al and Zinner et al reported that claudin-1 is mainly expressed near the basal layer region and co-stained with Tp63 in epithelial cells. 19,20 Additionally, Chang et al demonstrated that claudin-1 acts as an oncogene in cancer, driving oncogenesis and regulates proliferation in the head and neck squamous cell carcinoma. 21 We found claudin-1 was significantly up-regulated with basal cells' excessive proliferation, which suggests claudin-1 is possibly involved in the mechanism of epithelial cells' aberrant proliferation in NIP.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study has observed that claudin‐3 is predominantly localized in ciliated cells in vitro, 8 implying that the down‐regulation of claudin‐3 may be caused by the inhibition of ciliated cell differentiation in NIP. On the other hand, Biswas et al and Zinner et al reported that claudin‐1 is mainly expressed near the basal layer region and co‐stained with Tp63 in epithelial cells 19,20 . Additionally, Chang et al demonstrated that claudin‐1 acts as an oncogene in cancer, driving oncogenesis and regulates proliferation in the head and neck squamous cell carcinoma 21 .…”
Section: Discussionmentioning
confidence: 99%